Implementation of Religious Teacher Leadership in Cultivating Islamic Ethics in Madrasah - Solong, Najamuddin Petta; Mokodenseho, Sabil; Rohmah, Siti (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This research analyzes the implementation of religious teacher leadership in cultivating Islamic ethics at Madrasah Aliyah Negeri 1 Gorontalo City. This study employs a qualitative descriptive approach with a phenomenological framework. Data collection involves observation, interviews, and documentation. Data analysis follows four stages: condensation, coding, categorization, and theorization. The findings reveal that religious teachers can design, organize, guide, and supervise the inculcation of religious teachings, particularly in Islamic jurisprudence, thus emphasizing the manifestation of Islamic ethics, such as dress code, religious traditions, and Islamic interactions. However, the teachers' skills in critical thinking, collaboration, communication, and creativity have yet to integrate the practice of religion within them, both among teachers and students. This research underscores the importance of further studies to unveil comprehensive strategies for realizing Islamic ethics across various dimensions in the context of religious teacher leadership. These strategies should align with the student profile project of